Random forest-based bioavailable strontium isoscape for environmental and archaeological applications in central eastern Argentina and western Uruguay - Cinzia Scaggion; Tommaso Giovanardi; Daniel Loponte; Mirian Carbonera; Elena Armaroli; Sara Bernardini; Stefano Benazzi; Andrés Gascue; Alejandro Acosta; Giulia Marciani; Eugenio Bortolini; Anna Cipriani; et al. (PLoS ONE, 2025)
Bioavailable strontium (Sr) isoscapes are essential tools in studies on environmental processes, animal and human mobility and provenance. The success of these studies relies on the comparison between the measured 87Sr/86Sr isotope ratios of specimens and the spatial distribution of environmental bioavailable Sr isotopic signatures across geographical regions. A critical step of this process is the construction of reference maps that integrate environmental Sr isotopic data with geographical information. Here, we present a new bioavailable Sr dataset of 113 environmental samples, including plants and malacological samples collected from center-east Argentina (Paraná Delta, Pampa and Entre Ríos plains) as well as adjacent Uruguay, covering an area of approximately 122,500 km2. This dataset is further integrated with archaeological bioapatite data from the literature to construct the first random forest-based Sr isoscape of the region. Notably this area is on recent Quaternary (fluvial, marine and aeolian) sediments derived from the erosion of magmatic and metamorphic terrains with different Sr isotope composition from low 87Sr/86Sr ratios (about 0.706) to highly radiogenic signatures (>0.71), and heterogeneously transported in the Delta area by the rivers and in the high plains by wind and rivers. This isoscape offers a unique perspective on the Sr isotope distribution in a lithologically homogeneous region characterized by relatively young sedimentary sequences. This work represents a significant advancement in the development of Sr isoscapes, providing a fundamental tool for environmental and archaeological applications in South America.